HUBUNGAN KEHILANGAN GIGI DENGAN STATUS GIZI DAN KUALITAS HIDUP PADA PERKUMPULAN LANSIA DI DESA PENATAHAN KECAMATAN PENEBEL TABANAN - A.A Gde Wirasantika Adhiatman, Sari Kusumadewi, Putu Adiartha Griadhi (Faculty of Dentistry, Universitas Islam Sultan Agung, 2018)
Background: Health practitioners around the world are now dealing withincreasing health problems, including oral disease. One of them is tooth loss.Losing teeth can cause problems or disturbances in the main functions of teeth(mastication, aesthetics and phonetics). These conditions can be overcome byusing denture. If the loss of untreated teeth doesn’t restored using denture, it will cause the function of the missing tooth can not be restored, which will result in disruption of nutritional status and quality of life of the elderly. This study aimed to determine the relationship of tooth loss with nutritional status in elderly society in the Penatahan village Penebel Tabanan.Methods: The research was an observational analytic study with cross sectionalresearch design. Total sampling used with total sample 109 people. The datawere collected by filling the dental chart, measuring IMT and interview using theOHIP-14 questionnaire.Results: The results showed 65.1% respondents had loss <6 teeth, 42.2%respondents had obesity, 75.2% respondents observed poor quality of life. Dataanalyzed using kolmogorov smirnov obtained p = 0,952 for relationship betweentooth loss with nuturional status and p = 0.676 for relationship between useof denture with nutritional status. Chi square used to test relationship betweentooth loss with quality of life (p= 0,735) and use of denture with quality of lifeshowed p = 0,139.Conclusions: The conclusion is there is no relationship between tooth lossand use of denture with nutritional status and quality of life in elderly society inPenatahan Village Penebel Tabanan